SUSTAINABLE DEVELOPMENT OF KERALA; ITS ENVIRONMENTAL CHALLENGES - Noushad.K and Vasil Vafeeque .C.A.K (EPRA International Journal of Economic and Business Review, 2015)
Each year, millions of persons are forcibly displaced by development projects, whether dams, roads, reservoirs or oil, gas and mining projects. While such projects can bring enormous benefits to society, they also impose costs, which are often borne by its poorest and most marginalized members. For millions of people around the world, development has cost them their homes, their livelihoods, their health, and even their very lives. Impoverishment and disempowerment often become their lot, with particularly harsh consequences for women and children. Although internally displaced persons are often defined as those uprooted by conflict, human rights violations and natural or human- made disasters, they also include those displaced by development projects. Indeed, Robinson points out: “While victims of disaster, especially natural disaster generally are the focus of sympathetic attention and international aid (as are many of those displaced by conflict), the same cannot be said for victims of development-induced displacement, although the consequences may be comparably dire. In an effort to better understand the plight of those displaced by with internally displaced persons, our Project asked the author to development projects and the relationship of this kind of displacement to international human rights and humanitarian frameworks for dealing examine the nature and scope of development-induced displacement and to identify the international institutions and remedies that might prove effective in addressing this question. Researcher is most grateful to Court Robinson for the extensive research he has done and for his comprehensive report, which was reviewed at a meeting of international experts, held in Washington DC on December 5. The report’s recommendations will contribute to the international response to this major public policy challenge. In particular, we would note that the report calls for a global consultation that would bring together the development as well as human rights and humanitarian communities to harmonize operational guidelines and policies applicable to development-induced displacement.